Proceedings of the Fifth International Conference on Tangible, Embedded, and Embodied Interaction 2010
DOI: 10.1145/1935701.1935727
|View full text |Cite
|
Sign up to set email alerts
|

I'm in the game

Abstract: We have developed an embodied puppet interface that translates a player's body movements to a virtual character, thus enabling the player to have a fine grained and personalized control of the avatar. To test the efficacy and short-term effects of this control interface, we developed a two-part experiment, where the performance of users controlling an avatar using the puppet interface was compared with users controlling the avatar using two other interfaces (Xbox controller, keyboard). Part 1 examined aiming m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In other papers, the body might be linguistically absent, though ever present (and implicitly gendered in binary normative ways) visually [64]. As I have already mentioned the overt focus on white and light-skinned bodies, it appears almost cynical, that, within the corpus a green body (represented through a fictional avatar) is more easily found [80] than real-world black bodies. Virtual body representations are strongly normative through the options they offer; none of which include visible disability markers, or even just a fat 8 body (see, for an example where a body is directly virtually slimmed, [30]).…”
Section: Bodies With Technologiesmentioning
confidence: 90%
“…In other papers, the body might be linguistically absent, though ever present (and implicitly gendered in binary normative ways) visually [64]. As I have already mentioned the overt focus on white and light-skinned bodies, it appears almost cynical, that, within the corpus a green body (represented through a fictional avatar) is more easily found [80] than real-world black bodies. Virtual body representations are strongly normative through the options they offer; none of which include visible disability markers, or even just a fat 8 body (see, for an example where a body is directly virtually slimmed, [30]).…”
Section: Bodies With Technologiesmentioning
confidence: 90%
“…The game described herein is part of a research program called Tangibles for Augmenting Spatial Cognition (TASC), which aims to develop and study virtual game environments that employ tangible and embodied interaction in the context of solving spatial puzzles. The TASC team has examined various interactive methods for engaging distinct spatial skills, including mental rotation, perspective taking, and penetrative thinking (Mazalek et al, 2010;Chang et al, 2017aChang et al, , 2019. In previous TASC research, head-tracking, hand-tracking, tactile feedback, and a tangible interface were integrated in a custom VR environment that required users to solve spatial puzzles.…”
Section: Tangibles For Augmenting Spatial Cognitionmentioning
confidence: 99%
“…Two recent meta-analyses have estimated the effect size atд = 0.55 [6] andr = 0.18-0.26 [60]. Other studies have focused more on the training effects of these commercial games [18,23,33,50,62,63,65,68] or analyzed new games designed specifically for spatial skill training [17,45,79,82].…”
Section: Spatial Skills and Video Game Playmentioning
confidence: 99%
“…While very little is known empirically about which game features are spatially relevant, some preliminary steps in this direction have been taken by Wauck et al and Xiao et al, who found that performance on first person exploration and 3D object construction tasks within a computer game correlated with spatial skill [77,82]. In addition, Chang et al and Mazalek et al found that a first person exploration VR game with tangibles improved players' spatial skills in the short term [17,45]. Each of these in-game tasks map well to the Adventure and Puzzle genres and demonstrate how a synergy between spatially-relevant features and LSS population preferences might be achieved.…”
Section: Design Recommendationsmentioning
confidence: 99%